Design Techniques for the Optimal Creation of a Robot for Interaction with Children with Autism Spectrum Disorder - Cristofer Tamaral; Lidia Hernandez; Clara Baltasar; Jose San Martin (Machines)
Educational robotics is a sector that is being integrated into classrooms to achieve innovative and effective learning in the early stages of children’s education. However, it is not only applied in education but has great importance in its use with children with special needs to improve their quality of life. The convenience of robots applied to interaction with children with autism spectrum disorder (ASD) has been widely demonstrated. In this work, a study is carried out on what design patterns a robot focused on children with autism should have. It is necessary to make known the characteristics of this and, from there, how to apply these concepts to the effective design of a device. A robot, TEA-2, is proposed that encompasses all these guidelines in a single robot.